Cross-sectional study on hearing loss and auditory reaction time before and after spinal anesthesia with marcaine 0.5% in patients undergoing elective surgery - Vahabi, Sepideh (Ann Med Surg (Lond), 2020)
BACKGROUND: Hearing loss is a rarely reported complication of spinal anesthesia. The purpose of this study is to assess the effects of 0.5% Maracine (bupivacaine) on hearing threshold and auditory reaction time before and after spinal anesthesia among patients undergoing elective surgery. MATERIALS AND METHODS: This is a descriptive cross-sectional study performed on 60 patients undergoing elective surgery with ASA Class II and II anesthesia (0.5% bupivacaine) at Khorramabad Nursing Home. After obtaining consent from the patients, audiometry and tympanometry tests were performed using AZ80 and Madsen otoflex tympanometer and related findings including the presence or absence of hearing loss at various frequencies, before and after the surgery, were noted in a form for each patients along with their demographic data. SPSS 21 was used for statistical analysis and the data were analyzed using descriptive statistics and chi-square inferential tests. RESULTS: At low frequencies of 250 and 500 Hz, no significant difference in pre- and postoperative hearing threshold in the right ear (P > 0.05) was seen, but at frequencies above 500 Hz, the hearing threshold was significantly decreased after surgery, (P < 0.05). In the left ear at 250, 1000, 3000, and 8000 Hz, there was no significant difference (P > 0.05) between pre- and postoperative hearing threshold. The results of this study showed that the preoperative hearing threshold for men and women did not differ and the auditory threshold and auditory response time after surgery did not differ between the two sexes (P > 0.05). Similarly, the difference was not correlated with the age and the levels of anesthesia (P > 0.05). The results also showed that changes in mean arterial blood pressure (MAP) and heart rate above 30% of baseline were also not correlated with hearing loss (P > 0.05). CONCLUSIONS: The results showed that at certain frequencies, hearing loss was observed in both ears after spinal anesthesia with 5% Marcaine, but this hearing loss was not related to age, sex, and spinal anesthesia level. The results also showed that changes in mean arterial blood pressure (MAP) and heart rate above 30% of baseline did not correlate with hearing loss.